Serological and Molecular Investigation of Batai Virus Infections in Ruminants from the State of Saxony-Anhalt, Germany, 2018 - Cichon, Nicole; Eiden, Martin; Schulz, Jana; Günther, Anne; Wysocki, Patrick; Holicki, Cora M.; Borgwardt, Joachim; Gaede, Wolfgang; Groschup, Martin H.; Ziegler, Ute (Viruses, 2021)
Arthropod-borne Batai virus (BATV) is an Orthobunyavirus widely distributed throughout European livestock and has, in the past, been linked to febrile diseases in humans. In Germany, BATV was found in mosquitoes and in one captive harbor seal, and antibodies were recently detected in various ruminant species. We have, therefore, conducted a follow-up study in ruminants from Saxony-Anhalt, the most affected region in Eastern Germany. A total of 325 blood samples from apparently healthy sheep, goats, and cattle were tested using a BATV-specific qRT-PCR and SNT. Even though viral RNA was not detected, the presence of antibodies was confirmed in the sera of all three species: sheep (16.5%), goats (18.3%), and cattle (41.4%). Sera were further analyzed by a glycoprotein Gc-based indirect ELISA to evaluate Gc-derived antibodies as a basis for a new serological test for BATV infections. Interestingly, the presence of neutralizing antibodies was not directly linked to the presence of BATV Gc antibodies. Overall, our results illustrate the high frequency of BATV infections in ruminants in Eastern Germany.